Professional Legitimation for Education in Canadian Universities: The Canadian Journal of Education, 1976-1997 - Fisher, Donald (Canadian Journal of Education/Revue canadienne de l’éducation, 2017)
The history of the Canadian Society for the Study of Education (CSSE) has been profoundly influenced by changes in the role of the Canadian State. The introduction of social welfare legislation based on Keynesian economics was paralleled in the social sciences as the state adopted first a supportive role, then an active, interventionist role with regard to funding social science research. The inclusion of education in the social science field is set within the broader structural trends in society toward professionalization and utilitarianism. The dominance of human capital theory and the strategic component of the developing national science policy during the 1960s typify the latter trend. As in other industrialized societies, the aristocratic ideal of civility has been overtaken by the professional ideal, which according to Perkin (1989) is “based on trained expertise and selection by merit...[emphasizing] human capital rather than passive or active property, highly skilled and differentiated labour rather than the simple labour theory of value, and selection by merit defined as trained and certified expertise” (p. 4). The predominance of this ideal in modern society is clearly linked to the emergence of the interventionist state and its emphasis on the public good.